EVALUASI DAMPAK MORATORIUM PERIZINAN KAPAL EKS ASING TERHADAP HASIL TANGKAPAN NELAYAN LEBIH KECIL 30 GT DI BITUNG SULAWESI UTARA - Sulaeman Rusdi; Asbar Asbar; Danial Danial (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2018)
One of the policies issued by the Ministry of Maritime Affairs and Fisheries in anticipation of the occurrence of IUU Fishing is the moratorium policy of ex-foreign vessels as stipulated in Ministerial Regulation No. 56/2014. The presence of this policy is also one way to overcome the exploitation of Indonesia's marine resources. This study aims to determine the differences in fish catches smaller than 30 GT, knowing the impact of the moratorium policy on permits for ex-foreign vessels to catch smaller fishermen 30 GT and knowing the direction of fisheries resource management in the Republic of Indonesia fisheries management area RI) 716. The comparative analysis of the two samples correlated with the results turns out that there are differences in the level of catches of the smaller fishermen 30 GT before and after the moratorium (2013 and 2016). The impact of the moratorium on the licensing of ex-foreign vessels on fishermen has led to an increase in unemployment of local ABK and ex-foreign ship crews, while fishing vessels smaller than 30 GT have increased their catch. The fisheries resource management strategy in the fisheries management area (WPPRI) 716 is to build cooperation of all relevant agencies that allow access to capital and provide guidance in terms of increasing knowledge and skills to increase fishermen's catches by 30 GT to the direction of fisheries management.